Menjaga Kualitas Jamu Kunyit Asam Segar Industri Rumah Tangga X Yogyakarta dengan Penyimpanan Suhu yang Tepat Berdasarkan Kadar Kurkuminoid - Dian Eka Ermawati; Villian Septiana; Wisnu Kundarto; Anif Nur Artanti; Sholichah Rohmani; Heru Sasongko (Jurnal Pengabdian Pada Masyarakat, 2021)
IMPROVING THE QUALITY OF FRESH ACID TURMERIC JAMU OF HOME INDUSTRY X AT THE RIGHT TEMPERATURE STORAGE BASED ON CURCUMINOID CONCENTRATION. Tamarind turmeric herbal medicine contains about 10% curcuminoids, consisting of: 1-5% curcumin, demectosicurcumin and bisdemethoxy-curcumin. Curcuminoids are a group of phenolic compounds as antibacterial, anticholesterol and antioxidants. Home Industry (IRT) X in Yogyakarta produces fresh turmeric and sour herbal medicine and is sold via delivery via an online application. Handling and storage at inappropriate temperatures can affect curcuminoid levels in herbal medicine, so it is necessary to do research on curcuminoid levels at various temperatures to provide information on IRT X in particular and herbal medicine manufacturers in general. Samples of herbal turmeric acid IRT X Yogyakarta stored at room temperature (25±2°C), refrigerator temperature (4±2°C), and freezer temperature (-10±2°C), analyzed the levels of curcuminoids on variations in storage temperature manually. quantitative method with UV-Vis Spectrophotometry. The analysis begins with the manufacture of standard curves and assays which are replicated three times. The results showed that curcuminoid levels were affected by storage temperature. Samples of herbal turmeric acid IRT X Yogyakarta which were analyzed by UV-Vis spectrophotometry method obtained a standard curve of y = 0.009x + 0.025 with a value of r = 0.997. The results of curcuminoid levels at room temperature were 4.74±0.13; refrigerator temperature 4.85±0.22; and freezer temperature 5.18±0.22. The optimum temperature in the handling and storage of the tamarind turmeric herbal medicine is at low temperatures, namely the refrigerator temperature and freezer temperature to maintain the curcuminoid content in the herbal medicine.